Basal ganglia infarction and hemorrhage associated with subarachnoid hemorrhage after trauma in an adult patient: A case report - Jong Un Moon; Mina Kim; Myoung Soo Kim (Interdisciplinary Neurosurgery, 2023)
Although posttraumatic ischemic stroke in basal ganglia is well recognized in children, basal ganglia infarction after trauma in adult patients has rarely been reported. We recently encountered an adult patient presenting with traumatic subarachnoid hemorrhage (SAH), hematoma, and ischemic stroke of the basal ganglia after trauma. A 34-year-old woman presented to our emergency department after a head injury. She presented a drowsy mental state and mild dysarthria. Her Glasgow Coma Scale score was 12 (E3, V4, and M5). Right hemiparesis and right facial palsy were observed. Acute hemorrhage in the left lentiform nucleus, traumatic SAH in the left Sylvian fissure, and epidural hemorrhage on her right side were observed on computed tomography of the brain. Brain magnetic resonance (MR) imaging with diffusion-weighted and apparent diffusion coefficient mapping showed an acute infarct in the body of the left caudate nucleus and the upper portion of the left lentiform nucleus. Vessel wall MR imaging and MR angiography indicated no abnormal finding in the left middle cerebral artery (MCA). Stretching, distorting, and tearing of the lenticulostriate arteries (LSA) originating from the MCA after head trauma may lead to vasospasm or thrombus and result in infarction or hemorrhage in the basal ganglia.